Brecht on theatre : the development of an aesthetic - Willett, John (Plays and Playwrights, 2013)
This selection of Bertolt Brecht s critical writing charts the development of his thinking on theatre and aesthetics over four decades. The volume demonstrates how the theories of Epic Theatre and Alienation evolved, and contains notes and essays on the staging of The Threepenny Opera, Mahagonny, Mother Courage, Puntila, Galileo and many others of his plays. Also included is A Short Organum for the Theatre, Brecht s most complete statement of his revolutionary philosophy of the theatre. With over 32 pages of photographs of Brecht s productions and workshops, this is a key volume for Literature and Theatre Studies alike.